ASPEK HUKUM DALAM PEMBAGIAN WARIS PADA PASANGAN BERBEDA SUKU DI MASYARAKAT PEPADUN PADANG RATU: KAJIAN HUKUM ADAT DAN HUKUM ISLAM - Hadaiyatullah, Syeh Sarip; Ismail, Habib; Fikri, Arif; Burhanuddin, Ahmad; Mardiantari, Ani (Institut Agama Islam Ngawi, 2025)
This study aims to analyze the factors influencing the choice between Lampung customary law and Islamic law in inheritance distribution among inter-ethnic couples in the Pepadun community of Padang Ratu, Central Lampung Regency. Lampung customary law, which emphasizes family values and cooperation, is often the main guideline in inheritance distribution. However, in the context of inter-ethnic couples, tensions between the application of customary law and Islamic law often arise, especially in the distribution of inheritance rights which are more proportional according to Islamic law. This research employs a qualitative approach with in-depth interviews with customary leaders, religious leaders, and local community members, as well as field observations to explore inheritance practices. The results indicate that although customary law is dominant, customary deliberations involving family members and customary leaders play a significant role in integrating both legal systems. Moreover, Islamic law offers a fairer perspective in inheritance distribution, considering the rights of men, women, and children in a proportional manner. This study is expected to provide a deeper understanding of the dynamics of inheritance law in the Pepadun community and highlight the importance of deliberation in achieving social justice for all parties involved. Keywords: Lampung Customary Law, Islamic Law, Inheritance Distribution, Inter-Ethnic Couples, Customary Deliberation, Pepadun Community.